Shear-Induced and Nanofiber-Nucleated Crystallization of Novel Aliphatic–Aromatic Copolyesters Delineated for In Situ Generation of Biodegradable Nanocomposites - Hosseinnezhad, Ramin (Polymers (Basel), 2021)
The shear-induced and cellulose-nanofiber nucleated crystallization of two novel aliphatic–aromatic copolyesters is outlined due to its significance for the in situ generation of biodegradable nanocomposites, which require the crystallization of nanofibrous sheared inclusions at higher temperatures. The shear-induced non-isothermal crystallization of two copolyesters, namely, poly(butylene adipate-co-succinate-co-glutarate-co-terephthalate) (PBASGT) and poly(butylene adipate-co-terephthalate) (PBAT), was studied following a light depolarization technique. To have a deep insight into the process, the effects of the shear rate, shear time, shearing temperature and cooling rate on the initiation, kinetics, growth and termination of crystals were investigated. Films of 60 μm were subjected to various shear rates (100–800 s(−1)) for different time intervals during cooling. The effects of the shearing time and increasing the shear rate were found to be an elevated crystallization temperature, increased nucleation density, reduced growth size of lamella stacks and decreased crystallization time. Due to the boosted nucleation sites, the nuclei impinged with each other quickly and growth was hindered. The effect of the cooling rate was more significant at lower shear rates. Shearing the samples at lower temperatures, but still above the nominal melting point, further shifted the non-isothermal crystallization to higher temperatures. As a result of cellulose nanofibers’ presence, the crystallization of PBAT, analyzed by DSC, was shifted to higher temperatures.